Interactions Between Psychiatric Disorders and Inflammatory Skin Diseases - systematic review - Kacalak, Mateusz (Quality in Sport, 2025)
Introduction: Depression and anxiety are prevalent mental disorders often co-occurring with chronic inflammatory conditions such as psoriasis and atopic dermatitis. These associations suggest shared biological mechanisms, including immune dysregulation and persistent inflammation. Understanding these links is essential for developing integrated treatments addressing both psychiatric and dermatological symptoms. Aim of Study: This study explores shared pathomechanisms between depression, anxiety disorders, psoriasis, and atopic dermatitis. Materials and Methods: A systematic literature review was conducted using PubMed and Google Scholar. Articles published between 2019 and 2025 were analyzed to identify biological mechanisms linking psychiatric disorders with inflammatory skin diseases. Keywords included: "depression," "anxiety disorders," "psoriasis," "atopic dermatitis," "pathomechanism," and "inflammation." Conclusion: Findings underscore the interconnectedness of psychiatric and inflammatory skin disorders via common pathophysiological pathways. Targeted biological therapies and psychological interventions show promise in managing these comorbidities. Further research is required to enhance integrated care for affected patients.